HUBUNGAN TUNTUTAN PEKERJAAN TERHADAP KEJADIAN STRES KERJA PADA JURNALIS PEREMPUAN DI KOTA PALEMBANG - Parlinda, Mesi; Malaka, Tan; Novrikasari, Novrikasari (Politeknik Kesehatan Kemenkes Bengkulu, 2020)
Female journalists are very at risk of experiencing work stress due to the arduous and risky task of gathering information to make a story. Profession as a journalist who is always chased by deadlines and high mobility can cause stress. This study aims to analyze the risk factors for job stress in female journalists in Palembang City. The study used a cross-sectional design involving 85 female journalists in Palembang City who were randomly selected from March to June 2020. The data was collected through a Health Safety Executive (HSE) Management Standard Indicator Tools questionnaire as well as interviews and direct observation by psychologists. The analysis showed that there were 4 female journalists who experienced work stress (4.7%). The risk factor that affects job stress is job demands p-value = 0.005 (OR 0.833; 95% CI 0.697 - 0.997). From the results of interviews and direct observation by psychologists, it was found that all four respondents experienced a tendency for light work stress. The risk factors that most influence the incidence of job stress for female journalists in Palembang City are job demands and personality types. Age, marital status, number of children, length of work, years of service, desk coverage, control of work, social support, interpersonal relationships, roles and changes in the organization have no effect on job stress.